PENGARUH PERILAKU PEMIMPIN TERHADAP KINERJA KARYAWANPADA KANTOR GAPENSI KOTA KENDARI - Marjani Marjani (Universitas Muhammadiyah Kendari, 2017)
This study aims to describe and determine the effect on employee performance behavior of leaders in Kendari city GAPENSI Office. The sampling technique using saturated sampling technique, namely by taking all of the total population to be sampled totaling 38 people . Data analysis using simple linear regression analysis. The results showed that the behavior of the leader of a significant effect on the performance of employees in the office GAPENSI Kendari city. That is the behavior change towards a better leader by providing support and encouragement, response to complaints subordinate leader, the leadership of the response on the advice of subordinat , facility leadership to the creation of a cooperative relationship between subordinate , the response of the leadership over the work of subordinates and fault -led response to the success of the work of subordinates can improve employee performance when observed from the indicators work, the development of competenc, commitmen , additional tasks and critical events.